Social impact and interpretation of the geological collections of Helmis Natural History Museum of Zakynthos - Stoupathis, Konstantinos (Bulletin of the Geological Society of Greece, 2019)
The Helmis Natural History Museum is located in Zakynthos, in the village of Agia Marina Fagia, only twenty minutes distance from the centre of the city of Zakynthos. The enlargement of the private collection of Panagiotis Helmis, a collection of natural history that originally included natural history exhibits acquired by the collector to meet his needs, was a challenge for the exhibition of this collection in a museum environment. Moreover, the museum was founded to introduce to the visitors the value of nature, to present information on lesser known fauna and flora species of the island and to focus on geology exhibits.